Giant Enhancement of Internal Electric Field Boosting Bulk Charge Separation for Photocatalysis - Li, Jie (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.